A nickel-manganese oxide pincushion structure composite material, a preparation method and application thereof

CN121669262BActive Publication Date: 2026-10-23LIAONING UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511876030.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-12
Publication Date
2026-10-23
Estimated Expiration
2045-12-12

AI Technical Summary

Technical Problem

但过渡金属催化剂重复利用率低,且催化剂中金属离子容易浸出,导致造成二次污染,引入新的污染源;此外以Ag为代表的贵金属价格比较昂贵,在实际应用中也受到了较大的限制

Benefits of technology

[0016]本发明通过水热法成功制备了NiMn2O3(OH)4复合材料,将NiMn2O3(OH)4复合材料用于活化PMS降解有机污染物,该复合材料能够显著提高PMS降解有机污染物的效率。NiMn2O3(OH)4复合材料活化PMS对亚甲基蓝、罗丹明B和盐酸四环素均具有良好的降解能力。Ni能够显著降低NiMn2O3(OH)4复合材料中金属离子的浸出率,镍离子和锰离子的浸出率分别仅为12.18%和0.16%,避免了金属离子的浸出对环境造成二次污染。不仅如此,通过4次循环实验发现NiMn2O3(OH)4催化剂具有良好的稳定性与可重复使用性,其降解效率高达98%以上。本发明制备的NiMn2O3(OH)4复合材料为环境保护及资源可持续利用和降解有机污染物提供了新的研究方向。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121669262B_ABST
    Figure CN121669262B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of catalyst, in particular to a kind of nickel-manganese oxide pompon structure composite material and its preparation method and application, comprising the following steps: nickel chloride solution and potassium permanganate solution are mixed, after stirring, obtain mixture;Mixture is carried out hydrothermal reaction, after reaction, filter, take precipitate, after washing, drying, grinding, obtain NiMn2O3 (OH) 4 Composite material.The NiMn2O3 (OH) 4 Composite material prepared by the present application can significantly improve the efficiency of potassium peroxymonosulfate degrading organic pollutants;And Ni can significantly reduce the leaching rate of metal ions in NiMn2O3 (OH) 4 Composite material, avoid the secondary pollution caused by the leaching of metal ions to environment.After 4 cycles of experiments, the degradation efficiency of NiMn2O3 (OH) 4 Composite material activated PMS degrading organic pollutants is still as high as 98%, which proves that it has good stability and reusability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and more specifically, to a nickel-manganese oxide spherical composite material, its preparation method, and its application. Background Technology

[0002] Organic pollutants are a class of chemical substances that are difficult to degrade and can persist in the environment for a long time. They are widely derived from industrial emissions, agricultural pesticides, and discarded electronic equipment. The harm caused by organic pollutants is multifaceted, posing a threat not only to human health but also causing serious environmental pollution.

[0003] Advanced oxidation processes (AOPs) are a novel technology for treating recalcitrant pollutants, and their ability to efficiently degrade organic pollutants has made them a research hotspot. However, how to efficiently activate persulfate (PMS) to effectively remove organic pollutants remains a core issue in this field. Studies have found that iron and manganese oxides in groundwater can also activate PMS, promoting its degradation of organic pollutants. However, transition metal catalysts have low reusability, and metal ions in the catalysts are prone to leaching, leading to secondary pollution and the introduction of new pollution sources. Furthermore, precious metals, such as Ag, are relatively expensive, which significantly limits their practical application. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a nickel-manganese oxide velvet ball structure composite material, its preparation method, and its application.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a method for preparing a nickel-manganese oxide spherical composite material, comprising the following steps: Nickel chloride solution and potassium permanganate solution were mixed and stirred to obtain a mixture. The mixture was subjected to a hydrothermal reaction. After the reaction was completed, the mixture was filtered, and the precipitate was collected. The precipitate was washed, dried, and ground to obtain NiMn2O3(OH)4 composite material.

[0006] In the preparation method of the above nickel-manganese oxide fluff ball structure composite material, the molar ratio of NiCl2·6H2O and KMnO4 is 1:(1~2.5).

[0007] In the preparation method of the above nickel-manganese oxide fluffy ball structure composite material, the molar ratio of NiCl2·6H2O and KMnO4 is 1:2.

[0008] In the preparation method of the above-mentioned nickel-manganese oxide fluff ball structure composite material, the hydrothermal reaction temperature is 120~160℃ and the hydrothermal reaction time is 4~6h.

[0009] In the preparation method of the above-mentioned nickel-manganese oxide fluff ball structure composite material, the hydrothermal reaction temperature is 150℃ and the hydrothermal reaction time is 6h.

[0010] The preparation method of the above-mentioned nickel-manganese oxide fluff ball structure composite material is as follows: stirring conditions are 10~50℃ and stirring speed of 100~600rpm for 0.5~2h; drying conditions are 60~100℃ and drying for 6~12h.

[0011] In a second aspect, the present invention provides a nickel-manganese oxide spherical composite material prepared by the method described in any of the preceding embodiments.

[0012] In a third aspect, the present invention provides an application of the above-described nickel-manganese oxide spherical composite material in the catalytic degradation of organic pollutants.

[0013] The above application is carried out by adding the above-mentioned nickel-manganese oxide spherical composite material and potassium persulfate to wastewater containing organic pollutants to catalytically degrade the organic pollutants.

[0014] The above-mentioned nickel-manganese oxide spherical composite material is used in the catalytic degradation of organic pollutants, wherein the organic pollutants are one or more of methylene blue, rhodamine B, and tetracycline hydrochloride.

[0015] Beneficial effects of the present invention

[0016] This invention successfully prepared a NiMn2O3(OH)4 composite material via a hydrothermal method. The NiMn2O3(OH)4 composite material was used to activate PMS for the degradation of organic pollutants, and this composite material significantly improved the efficiency of PMS in degrading organic pollutants. The NiMn2O3(OH)4 composite material activated PMS showed good degradation capabilities for methylene blue, rhodamine B, and tetracycline hydrochloride. Ni significantly reduced the leaching rate of metal ions in the NiMn2O3(OH)4 composite material; the leaching rates of nickel and manganese ions were only 12.18% and 0.16%, respectively, avoiding secondary pollution to the environment caused by metal ion leaching. Furthermore, through four-cycle experiments, the NiMn2O3(OH)4 catalyst exhibited good stability and reusability, with a degradation efficiency exceeding 98%. The NiMn2O3(OH)4 composite material prepared in this invention provides a new research direction for environmental protection, sustainable resource utilization, and the degradation of organic pollutants. Attached Figure Description

[0017] Figure 1The XRD patterns are of MnO2 prepared in Comparative Example 1 and NiMn2O3(OH)4 composite materials prepared in Examples 4-9; Curve a: MnO2, Curve bg: NiMn2O3(OH)4 (b: Example 4, c: Example 5, d: Example 6, e: Example 7, f: Example 8, g: Example 9).

[0018] Figure 2 This is a SEM image of MnO2 prepared in Comparative Example 1.

[0019] Figure 3 These are SEM images of the NiMn2O3(OH)4 composite materials prepared in Examples 1-9 (a: Example 1, b: Example 2, c: Example 3, d: Example 4, e: Example 5, f: Example 6, g: Example 7; h: Example 8, i: Example 9).

[0020] Figure 4 The results are EDS elemental analysis results of the NiMn2O3(OH)4 composite materials prepared in Examples 1(a) and 6(b).

[0021] Figure 5 These are XPS images of the NiMn2O3(OH)4 composite material prepared in Example 5; (a) Mn 3s, (b) Mn 2p, (c) Ni 2p, (d) O 1s.

[0022] Figure 6 The degradation efficiency curves of NiMn2O3(OH)4 composite materials prepared under different hydrothermal reaction times in Examples 4-6 for MB and the corresponding UV-Vis absorption spectra measured by catalytic degradation experiments are shown; (a) Degradation efficiency curve, (bd) UV-Vis absorption spectra (b: Example 4, c: Example 5, d: Example 6).

[0023] Figure 7 The degradation efficiency curves of MB for different reaction systems and the corresponding UV-Vis absorption spectra measured by catalytic degradation experiments are shown; (a) Degradation efficiency curve, (bd) UV-Vis absorption spectra (b: control group, c: Example 5, d: Comparative Example 1).

[0024] Figure 8 The degradation efficiency curves of RhB in different reaction systems and the corresponding UV-Vis absorption spectra measured in the catalytic degradation experiment are shown; (a) Degradation efficiency curve, (bd) UV-Vis absorption spectra (b: control group, c: Example 5, d: Comparative Example 1).

[0025] Figure 9The degradation efficiency curves of TCH in different reaction systems and the corresponding UV-Vis absorption spectra measured in the catalytic degradation experiments are shown; (a) Degradation efficiency curve, (bd) UV-Vis absorption spectra (b: control group, c: Example 5, d: Comparative Example 1).

[0026] Figure 10 The curves showing the degradation efficiency of RhB by the NiMn2O3(OH)4 composite material prepared in Example 8 are shown.

[0027] Figure 11 The curves showing the degradation efficiency of RhB by the NiMn2O3(OH)4 composite material prepared in Example 9 are shown.

[0028] Figure 12 This describes the effect of the free radical quencher of the NiMn2O3(OH)4 composite material prepared in Example 5 on the degradation rate of MB.

[0029] Figure 13 These are XRD patterns of the NiMn2O3(OH)4 composite material prepared in Example 5 before and after the catalytic cyclic degradation experiment.

[0030] Figure 14 These are SEM images of the NiMn2O3(OH)4 composite material prepared in Example 5 before and after the catalytic cyclic degradation experiment; (a) before the experiment, (b) after the experiment.

[0031] Figure 15 The results are the catalytic stability test results of the NiMn2O3(OH)4 composite material prepared in Example 5 for activating PMS to degrade MB. Detailed Implementation

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0033] Unless otherwise stated, scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. Unless otherwise specified, the experimental methods used in the examples are conventional methods. Where specific conditions are not specified in the examples, they should be performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0034] Example 1: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material is 1:2 (0.5h).

[0035] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 3 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 0.5 hours. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 60–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn₂O₃(OH)₄ composite material.

[0036] Example 2: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material is 1:2 (1h).

[0037] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 3 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 1 hour. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 60–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn2O3(OH)4 composite material.

[0038] Example 3: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material was 1:2 (2h).

[0039] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 3 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 2 hours. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 60–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn2O3(OH)4 composite material.

[0040] Example 4: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material is 1:2 (4h).

[0041] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 3 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 4 hours. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 50–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn2O3(OH)4 composite material.

[0042] Example 5: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material is 1:2 (6h).

[0043] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 3 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 6 hours. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 60–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn2O3(OH)4 composite material.

[0044] Example 6: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material was 1:2 (8h).

[0045] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 3 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 8 hours. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 60–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn2O3(OH)4 composite material.

[0046] Example 7: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material was 1:1 (6h).

[0047] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 1.5 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 6 hours. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 60–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn2O3(OH)4 composite material.

[0048] Example 8: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material was 1:1.5 (6h).

[0049] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 2.25 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 6 hours. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 60–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn2O3(OH)4 composite material.

[0050] Example 9: The molar ratio of NiCl2·6H2O and KMnO4 in the nickel-manganese oxide spherical composite material was 1:2.5 (6h).

[0051] A method for preparing a nickel-manganese oxide fluffy ball structure composite material includes the following steps: S1. Dissolve 1.5 mmol of nickel chloride hexahydrate in 30 mL of deionized water to obtain a nickel chloride solution; S2. Dissolve 3.75 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution; S3. Mix the nickel chloride solution and potassium permanganate solution and stir for 1 hour. After homogenizing the system, transfer the mixture to a 100 mL sealed autoclave and react at 150 °C for 6 hours. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry the product in a drying oven at 60–100 °C for 6–12 hours. Grind the dried solid powder to obtain the NiMn2O3(OH)4 composite material.

[0052] Comparative Example 1: Preparation of MnO2

[0053] The preparation method of MnO2 includes the following steps: S1. Dissolve 3 mmol of potassium permanganate in 30 mL of deionized water to obtain a potassium permanganate solution and stir for 1 h; S2. Transfer the potassium permanganate solution to a 100 mL sealed autoclave and react at 150 °C for 6 h. After the reaction is complete, allow it to cool naturally. Filter the reaction product and wash it with anhydrous ethanol and deionized water. Dry it in a drying oven at 60–100 °C for 6–12 h, and grind the dried solid powder to obtain MnO2.

[0054] Characterization analysis of NiMn2O3(OH)4 in Example 10

[0055] 1. Crystal structure analysis of NiMn2O3(OH)4

[0056] Figure 1The XRD patterns are of the MnO2 prepared in Comparative Example 1 and the NiMn2O3(OH)4 catalysts prepared in Examples 4-9. Curve a is the XRD pattern of the sample (MnO2) synthesized without the addition of nickel chloride hexahydrate. The diffraction peaks at 2θ = 12.3°, 24.8°, 36.6° and 65.5° correspond to the (003), (006), (101) and (110) crystal planes of δ-MnO2 (JCPDS No. 86-0666), respectively. Curves b to g are the XRD patterns of NiMn2O3(OH)4 prepared in Examples 4 to 9. The diffraction peaks at 2θ = 18.5°, 36.7° and 65.5° correspond to the (002), (200) and (220) crystal planes of NiMn2O3(OH)4 (JCPDS No. 42-1319), respectively. These diffraction peaks confirm the successful synthesis of the NiMn2O3(OH)4 catalyst. Comparing curves b to d, it can be seen that the intensity of the diffraction peak of NiMn2O3(OH)4 gradually increases with the extension of hydrothermal reaction time, indicating that the crystallinity of the catalyst has been improved. Comparing curves c and e to g, it can be seen that when the molar ratio of NiCl2·6H2O to KMnO4 increases from 1:1 to 1:2.5, diffraction peaks of the (002), (200), and (220) crystal planes of NiMn2O3(OH)4 (JCPDS No. 42-1319) still appear at positions of 2θ=18.5°, 36.7°, and 65.5°. These diffraction peaks confirm the successful synthesis of the NiMn2O3(OH)4 catalyst. At the same time, the intensity of the δ-MnO2 diffraction peak is very weak or almost disappears in curves b to g. This may be due to the fact that some Mn2O3(OH)4 is lost during the hydrothermal process. 4+ Be Ni 2+ The substitution resulted in a NiMn2O3(OH)4 spherical structure. Furthermore, no other impurity peaks were found in the XRD pattern, indicating that the prepared catalyst has high purity and is suitable for further research and application.

[0057] 2. Morphology and composition analysis of NiMn2O3(OH)4

[0058] Figure 3 These are SEM images of NiMn2O3(OH)4 prepared in Examples 1-9. Figure 3 As can be seen from a to 3f, with the extension of hydrothermal reaction time, the diameter of the spherical NiMn2O3(OH)4 catalyst gradually increases, and the density of the structure improves. When the hydrothermal reaction time is 0.5 h, the NiMn2O3(OH)4 catalyst is a small spherical structure with an average diameter of 0.48~0.52 μm. Figure 3 a); When the hydrothermal reaction time reaches 4~6 hours ( Figure 3d, 3e), the spherical structure of NiMn2O3(OH)4 catalyst surface has grown flower-like leaves and exhibits uniform and distinct morphological features; hydrothermal reaction time 8h ( Figure 3 The spherical structure of the catalyst in f) has changed. Although the spherical structure is still maintained, slight agglomeration of the surface blades has begun to appear, and the spherical blades on the catalyst surface have become denser. Figure 3 As can be seen from g~3i, when the molar ratio of NiCl2·6H2O and KMnO4 increases from 1:1 to 1:2.5, the size of the pom-pom gradually increases, but the pom-pom leaves still maintain a uniform and distinct morphological characteristics. Figure 2 This is the SEM image of MnO2 prepared in Comparative Example 1. Individual MnO2 exhibits a small flower-like spherical structure, but no obvious velvety spherical structure was observed. This comparison further confirms that the introduction of Ni ions plays a decisive role in forming the NiMn2O3(OH)4 catalyst with a specific morphology. Figure 4 a and 4b are the EDS elemental analysis results of the NiMn2O3(OH)4 catalysts obtained in Example 1 with a hydrothermal reaction time of 0.5 h and Example 5 with a hydrothermal reaction time of 6 h, respectively. The presence of Mn, Ni and O elements in the figures further confirms the successful preparation of the NiMn2O3(OH)4 catalyst.

[0059] 3. XPS analysis of NiMn2O3(OH)4

[0060] To further verify the valence states of each element in the material, we performed XPS analysis on NiMn2O3(OH)4 from Example 5, which underwent a hydrothermal reaction at 150°C for 6 hours. The results are as follows: Figure 5 As shown, by Figure 5 From a and 5b, we know that Mn 2p 3 / 2 With Mn2p 1 / 2 The distance between the two spectral peaks is approximately 11.4 eV, and the energy level difference between the two peaks in the Mn 3s spectrum is approximately 4.8 eV, indicating that the Mn in the composite material is in the +4 oxidation state. Figure 5 The two spectral peaks at 854.88 eV and 872.68 eV in b represent Ni 2p... 3 / 2 and Ni2p 1 / 2 The characteristic peaks of Ni. The two spectral peaks at 860.88 eV and 879.28 eV are the corresponding satellite peaks of nickel, usually caused by multiple splitting of transition metal energy levels, and are used to prove that Ni... 2+ The existence of. Figure 5 The three spectral peaks of O 1s in d at 529.3 eV, 530.7 eV, and 532.1 eV correspond to the O 1s of the metal oxide, respectively. latt O sur and O absThe above results further confirm the successful preparation of the NiMn2O3(OH)4 catalyst.

[0061] Test Example 1: Performance Test of NiMn2O3(OH)4 Activated PMS for Degrading Multiple Organic Pollutants

[0062] 1. Catalytic degradation experiment

[0063] Multiple pollutants were targeted for degradation: MB (RhB or TCH) was catalytically degraded in a 250 mL beaker under constant temperature of 25℃. 30 mg of catalyst was dispersed in 100 mL (20 mg / L) of MB (RhB or TCH) solution (MB and RhB aqueous solution pH=7, TCH aqueous solution pH=4.2), and the mixture was magnetically stirred for 30 min. When the solution reached adsorption-desorption equilibrium, a 4 mL sample was taken, and the catalyst was immediately removed using a filter before being placed in a centrifuge tube for later use (0 min). Subsequently, 18 mg of PMS was added to the reaction solution, and a 3 mL sample was taken within a certain reaction time. The reaction solution was quenched with 1 mL (0.1 mol / L) of sodium thiosulfate, and the catalyst was removed using a 0.45 μm filter. The obtained solution was then placed in a centrifuge tube for later use. Finally, the absorbance of the reaction solution was measured using a UV-Vis spectrophotometer at an absorption wavelength of 663 nm (553 nm or 356 nm). Unless otherwise specified, the following catalytic performance tests shall be conducted in accordance with the experimental methods provided above.

[0064] 2. Results of Catalytic Experiments

[0065] 2.1 NiMn2O3(OH)4 Catalytic Degradation of Methylene Blue (MB) Prepared with Different Hydrothermal Reaction Times

[0066] To verify the catalytic performance of NiMn2O3(OH)4 prepared at different reaction times, this experiment tested the catalytic performance of NiMn2O3(OH)4 prepared in Examples 4-6 using MB as the target pollutant. Finally, the absorbance of the reaction solution was measured at an absorption wavelength of 663 nm using a UV-Vis spectrophotometer.

[0067] Figure 6 The curves show the degradation efficiency of NiMn2O3(OH)4 on MB prepared with different hydrothermal reaction times. Based on... Figure 6 It can be seen that the degradation rate of MB by the NiMn2O3(OH)4 catalyst after 8 hours is lower than that of the NiMn2O3(OH)4 catalysts after 4 hours and 6 hours. Observation shows that the degradation efficiency of the 4-hour and 6-hour catalysts is very similar, with degradation rates of 95.2% and 94.4%, respectively. Figure 6 b~6d are the UV-Vis absorption spectra of PMS degrading MB activated by NiMn2O3(OH)4 catalyst. Figure 6 The characteristic peak value of MB in b~d (λ) max The wavelengths of NiMn₂O₃(OH)₄ (663 nm) shifted to 613 nm, 601 nm, and 610 nm, respectively. The degree of blue shift clearly indicates that the 6-hour NiMn₂O₃(OH)₄ catalyst is more effective in activating PMS for MB degradation. Catalyst yield is also a factor to consider; the yield of the 4-hour NiMn₂O₃(OH)₄ catalyst is significantly lower than that of the 6-hour catalyst. Therefore, a hydrothermal reaction time of 6 hours for NiMn₂O₃(OH)₄ is the optimal catalyst.

[0068] 2.2 Catalytic degradation of MB in different reaction systems

[0069] In this experiment, the catalytic performance of NiMn2O3(OH)4 prepared in Example 5 and MnO2 prepared in Comparative Example 1 was tested using MB as the target pollutant. A PMS system without any catalyst was used as a control group. Finally, the absorbance of the reaction solution was measured at an absorption wavelength of 663 nm using a UV-Vis spectrophotometer.

[0070] Figure 7 The graphs show the degradation rate curves of MB in different reaction systems. As can be observed from Figure 7a, the degradation rates of NiMn2O3(OH)4 and MnO2 prepared by hydrothermal reaction for 6 hours are extremely similar at 10 minutes. It is clear that the adsorption effect of MnO2 is greater than its catalytic effect. The addition of Ni ions alters the morphology of MnO2, thus reducing the adsorption of the complex. The catalytic effect of NiMn2O3(OH)4 is far greater than its adsorption effect. Observing the color during the MB degradation process, it was found that MnO2 turned a deep blue after adding PMS for 5 minutes, indicating that MnO2 desorbed after reaching adsorption equilibrium. The UV-Vis absorption spectra of the NiMn2O3(OH)4 / PMS-MB system were analyzed. Figure 7 c) Analysis showed that after 5 minutes of PMS introduction into the system, the absorption peak intensity of MB significantly decreased, accompanied by a significant blue shift. After 20 minutes, the degradation rate of MB reached 99.5%. In contrast, PMS alone did not cause a blue shift in MB. Figure 7 b). This blue shift phenomenon originates from the efficient activation of PMS by NiMn2O3(OH)4, which promotes the generation of active groups and subsequently triggers N-demethylation of MB molecules. The newly appearing 601 nm characteristic peak represents the intermediate product of MB degradation, thiophene (C... 12 H 10 N3S), which is the hallmark peak of complete N-demethylation of MB.

[0071] 2.3 Catalytic degradation of Rhodamine B (RhB) in different reaction systems

[0072] In this experiment, RhB was used as the target pollutant to test the catalytic performance of NiMn2O3(OH)4 prepared in Example 5 and MnO2 prepared in Comparative Example 1, while the PMS system without any catalyst was used as a control group. Finally, the absorbance of the reaction solution was measured at an absorption wavelength of 553 nm using a UV-Vis spectrophotometer.

[0073] Figure 8 These are the rate curves of RhB degradation in different reaction systems, through... Figure 8 It can be observed that, within 30 minutes, NiMn₂O₃(OH)₄ exhibits significantly better degradation of RhB than MnO₂. NiMn₂O₃(OH)₄ can degrade most of the RhB within 30 minutes, while MnO₂ requires 150 minutes for complete degradation. This further demonstrates the high efficiency of NiMn₂O₃(OH)₄ in degrading RhB dyes. The color change during the degradation process also clearly shows that NiMn₂O₃(OH)₄ has a rapid degradation rate for RhB. Figure 8 The UV-Vis absorption spectrum of NiMn2O3(OH)4 / PMS-RhB shown in c indicates that after 5 min of PMS addition, the absorption peak intensity of RhB decreases significantly, accompanied by a noticeable blue shift. Within 30 min, the degradation rate of RhB reaches 98.2%, while PMS itself does not cause a blue shift in RhB. Figure 8 (b) This blue shift phenomenon may be because NiMn2O3(OH)4 can rapidly activate PMS, generating active groups that quickly degrade RhB. It is evident that the NiMn2O3(OH)4 system also exhibits a significant advantage in RhB degradation.

[0074] 2.4 Catalytic degradation of tetracycline hydrochloride (TCH) in different reaction systems

[0075] In this experiment, TCH was used as the target pollutant to test the catalytic performance of NiMn2O3(OH)4 prepared in Example 5 and MnO2 prepared in Comparative Example 1, while the PMS system without any catalyst was used as a control group. Finally, the absorbance of the reaction solution was measured at an absorption wavelength of 356 nm using a UV-Vis spectrophotometer.

[0076] Figure 9The graph shows the degradation rate curves of TCH in different reaction systems. As can be observed from Figure 9a, only PMS can rapidly decrease the TCH concentration and then maintain it at that concentration. Compared with PMS, the degradation effects of NiMn2O3(OH)4 / PMS and MnO2 / PMS systems did not improve. Furthermore, the three degradation systems showed an intersection point at 60 min of degradation reaction. This indicates that after PMS was introduced into the reaction system, NiMn2O3(OH)4 and MnO2 catalysts did not play the expected catalytic role in the degradation of TCH. The UV-Vis absorption spectrum of NiMn2O3(OH)4 / PMS-TCH was also observed. Figure 9 c) After adding PMS for 5 minutes, the absorption peak of TCH significantly decreased, but no blue shift was observed. This indicates that during this period, NiMn2O3(OH)4 mainly played an adsorption role, and MnO2 had a similar effect on TCH. In summary, NiMn2O3(OH)4, as a catalyst, is far more effective than TCH in degrading MB and RhB, with the degradation effect in the order of MB > RhB > TCH.

[0077] 2.5 NiMn2O3(OH)4 Catalytic Degradation of RhB Prepared with Different Molar Ratios of NiCl2·6H2O and KMnO4

[0078] Experimental Method: RhB was catalytically degraded in a 250 mL beaker at a constant temperature of 25℃. 10 mg of catalyst was dispersed in 100 mL (10 mg / L) RhB solution (pH=7), and the mixture was magnetically stirred for 30 min. When the solution reached adsorption-desorption equilibrium, a 4 mL sample was taken, and the catalyst was immediately removed using a filter before being placed in a centrifuge tube for later use (0 min). Subsequently, 10 mg of PMS was added to the reaction solution, and a 3 mL sample was taken within a certain reaction time. The reaction solution was quenched with 1 mL (0.1 mol / L) sodium thiosulfate, and the catalyst was removed using a 0.45 μm filter. The obtained solution was then placed in a centrifuge tube for later use. Finally, the absorbance of the reaction solution was measured at an absorption wavelength of 553 nm using a UV-Vis spectrophotometer. This experiment tested the catalytic performance of NiMn2O3(OH)4 prepared in Examples 8-9 using RhB as the target pollutant. The test results are as follows: Figures 10-11 As shown.

[0079] 3. Mechanism of PMS degradation by NiMn2O3(OH)4 catalyst activation

[0080] 3.1 Free radical quenching experiment

[0081] To further investigate the degradation mechanism of MB by activated PMS using NiMn2O3(OH)4, we designed a series of quenching experiments using NiMn2O3(OH)4 prepared in Example 5 as the catalyst for PMS degradation. The quenching agents used in the quenching experiments were tert-butanol (TBA), chloroform (CHCl3), methanol (MeOH), and furfuryl alcohol (FFA), which were used to capture different active species. The experimental results are shown below. Figure 12 As shown. TBA is used for clearing OH, CHCl3 is used to remove O2. - MeOH can be used not only to remove OH can also remove SO4 - Choose to remove SO4 using MeOH - This is because MeOH reacts with SO4. - Its elimination effect is several times that of TBA; FFA is used for elimination. 1 O2.

[0082] The results of the quenching experiment show that... OH, SO4 - and O2 - All of them played a relatively weak role in the degradation process. The inhibitory performance of the quenchers on MB degradation followed the order of FFA > TBA > MeOH > CHCl3, with FFA showing particularly prominent inhibition, indicating that during the degradation process... 1 O2 plays a major role in the degradation of MB. Therefore, the degradation process of MB follows this pathway: first, N-demethylation occurs, followed by the decomposition of the aromatic ring structure, ultimately generating CO2, H2O, and several small molecule compounds.

[0083] 3.2 Reproducibility of NiMn2O3(OH)4 catalyst

[0084] The reusability of a catalyst is an important indicator for its industrial application. Using NiMn2O3(OH)4 prepared in Example 5 as the catalyst for PMS degradation, four catalytic cycle experiments were conducted, following the experimental methods described in Test Example 1.

[0085] Figure 13 The XRD patterns of the NiMn2O3(OH)4 spherical catalyst before and after the degradation of MB are shown in the figure. The data in the figure show that the XRD patterns of the NiMn2O3(OH)4 catalyst remain stable before and after the degradation reaction, with no significant changes, indicating that the catalyst has excellent structural stability.

[0086] Figure 14 These are SEM images of the NiMn2O3(OH)4 spherical catalyst before and after the reaction. By carefully observing these images, we can clearly see that NiMn2O3(OH)4 maintains the same morphology and size before and after the reaction, which indicates that the NiMn2O3(OH)4 catalyst has good morphological stability.

[0087] Figure 15 This study revealed the results of four rounds of degradation experiments on MB using the NiMn2O3(OH)4 spherical catalyst under constant conditions. Experimental data showed that even after four repetitions following the addition of PMS to the reaction system for 30 minutes, the degradation efficiency of NiMn2O3(OH)4 for MB remained above 98%. This indicates that the NiMn2O3(OH)4 catalyst possesses excellent catalytic stability and recyclability, demonstrating its promising potential in the treatment of MB organic wastewater.

[0088] In addition, we performed ICP analysis on the solution of MB degradation by NiMn2O3(OH)4 catalyst. The results showed that the leaching rates of nickel ions and manganese ions were 12.18% and 0.16%, respectively. This further proves that NiMn2O3(OH)4 catalyst has good stability and reusability, which provides a solid foundation for its widespread application in practice.

[0089] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. The application of a nickel-manganese oxide spherical composite material in the catalytic degradation of organic pollutants, characterized in that, The method is as follows: In wastewater containing organic pollutants, nickel-manganese oxide spherical composite material and potassium persulfate are added to catalytically degrade the organic pollutants; the organic pollutants are methylene blue and rhodamine B. The preparation method of the nickel-manganese oxide velvet ball structure composite material includes the following steps: Nickel chloride solution and potassium permanganate solution were mixed and stirred to obtain a mixture. The mixture was subjected to a hydrothermal reaction for 4-6 hours. After the reaction was completed, the mixture was filtered, the precipitate was collected, and the precipitate was washed, dried, and ground to obtain NiMn2O3(OH)4 composite material. The molar ratio of NiCl2·6H2O to KMnO4 is 1:1~2.

5.

2. The application of the nickel-manganese oxide spherical composite material according to claim 1 in the catalytic degradation of organic pollutants, characterized in that, The molar ratio of NiCl2·6H2O to KMnO4 is 1:

2.

3. The application of the nickel-manganese oxide spherical composite material according to claim 1 in the catalytic degradation of organic pollutants, characterized in that, The hydrothermal reaction temperature is 120~160℃.

4. The application of the nickel-manganese oxide spherical composite material according to claim 1 in the catalytic degradation of organic pollutants, characterized in that, The hydrothermal reaction temperature was 150℃, and the hydrothermal reaction time was 6 hours.

5. The application of the nickel-manganese oxide spherical composite material according to claim 1 in the catalytic degradation of organic pollutants, characterized in that, The stirring conditions are: stirring at 100-600 rpm for 0.5-2 hours at 10-50℃; the drying conditions are: drying at 60-100℃ for 6-12 hours.

Citation Information

Patent Citations

  • Composite manganese oxide catalyst for synchronously removing VOCs (Volatile Organic Compounds) and NOx in medium and low temperature flue gas as well as preparation method and application of composite manganese oxide catalyst

    CN114768794A